Content and Essence of Vitagen Educational Technology - Samatova Iroda Azamjon qizi (Scientific Trends, 2024)
This article highlights the basic competencies of secondary schools based on international educational standards, the basic competencies of secondary schools, the use of vitagenic education technologies in the development of social competencies among students, the content, significance, pedagogical and psychological conditions of vitagenic education technologies in ensuring the effectiveness of the educational process in our republic.
Keywords: Vitagenic education technologies, qualification requirement, social competence, basic competencies, students, social competence, motivation of educational activity, creating a situation of success.